Constructing Intrinsically Safe Lithium-Ion Battery Energy Storage via Gradient-Laminated Ceramifiable Silicone Foams - Qiu, Shuilai; Xu, Jingyao; Shi, Congling; Zhang, Laibin (Nano-Micro Letters, 2026)
Achieving high safety in energy storage systems is paramount but hindered by the catastrophic risks of thermal runaway propagation (TRP). This study develops a gradient-laminated ceramifiable silicone foam composite to resolve the inherent trade-off between thermal insulation and dynamic impact toughness. By integrating a polydimethylsiloxane foam matrix with a load-bearing glass fiber fabric skeleton, the material utilizes silane coupling agents for robust interfacial adhesion, while multiscale fillers promote synergistic ceramicization. Characterization reveals robust mechanical durability, maintaining stable elasticity across a wide temperature range (− 40 to 300 °C) and retaining 93% residual stress after 1,000 compression cycles. Under extreme thermal exposure, the foam transforms into a dense ceramic barrier, reducing total heat release by 54.4% and sustaining thermal protection for over 30 min. Crucially, during battery module testing, this architecture efficiently intercepts high-velocity gas jets and confines thermal runaway to a single cell. Fabricated via a scalable process, this composite paves a viable way for constructing intrinsically safe energy storage systems. Highlights: 1 A gradient laminated architecture is engineered to resolve the intrinsic trade off between thermal insulation and impact toughness via synergistic ceramization. 2 The composite exhibits exceptional fatigue resistance with 93% stress retention and stable elasticity across a wid e temperature range ( from 40 to 300 °C). 3 The formed dense ceramic barrier effectively intercepts high pressure gas jets, confining thermal runaway to a single cell in battery modules.